Hubungan Volume Oksigen Maksimal dengan Denyut Nadi Istirahat Fase Pertumbuhan Dewasa Muda - Ilham Ramadhan; Rizki Amalia Nurfitriani; Sinu andhi jusup; Lukman aryoseto (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Maximal oxygen uptake is a measure of cardiorespiratory capacity that shows human body fitness. Resting heart rate shows the ability of the heart to pump blood throughout the body thus resting heart rate related to the maximum oxygen volume. The young adult is an important phase of human in determining the productivity of the level of life. Maximum oxygen volume can be related to resting heart rate, but this has not been studied in detail regarding the relationship between maximal oxygen volume and resting heart rate in young adults. The purpose of this study was to determine the relationship between maximal oxygen volume and resting heart rate of young adults. This research uses cross sectional method. The number of research samples was 38 students from the Faculty of Medical Education, Sebelas Maret University (UNS). The dependent variable tested in this study was resting pulse rate and the independent variable was maximal oxygen volume. The research was conducted at the Physiology Laboratory of Sebelas Maret University, Surakarta. Resting heart rate was calculated by sleeping position in the supine position for 15 minutes then measured by pulse oximetry and maximal oxygen volume was calculated by Astrand-Rhyming Step Test. The results showed that the data were normally distributed so that the Pearson correlation test could be performed. The results of the correlation test showed that the value of p = 0.000 (p < 0.05) which indicated there was a significant correlation between the two variables tested and the Pearson correlation value of - 0.612 which indicated a negative correlation with a strong correlation strength. This study concludes that there is a significant correlation between maximal oxygen volume and heart rate of young adults with a negative correlation.